Semantic affix rivalry: the case of Portuguese nominalisers - Rodrigues, Alexandra Soares (2015)
In Portuguese there are different suffixes that permit to construct event deverbal nouns (EDN) from the same base verb. Albeit deriving event nouns, the meanings of the derivatives of these suffixes are slightly different. We intend to contribute to the understanding of the mechanisms that are involved in affix semantic rivalry, specifically to the knowledge of the semantic features of the verbal base that are sensitive to the semantics of each affix. In a Lexicalist framework (e.g. Halle (1973) and Scalise (1984)), each base has idiosyncratic information on the affix(es) it may select. Other descriptions have challenged that traditional account, searching for systematic features that may relate classes of bases with certain affixes. One of those descriptions is, for instance, Fábregas (2010), according to which the affix selection depends on the internal argument of the verb (verbs with rheme path objects choose -da/-do and verbs with undergoers select -miento). The analysis of Portuguese data does not corroborate Fábregas’ hypothesis. Verbs with a rheme path object (descer ‘to lower, to take down’) present deverbal nouns with the suffix -mento (descimento ‘event of lowering, taking something down’). Verbs with an undergoer as internal argument (esfriar ‘to cool’, engordar ‘to fatten’) originate deverbal nouns in -da (esfriada ‘event of cooling’, engordada ‘event of fattening’). This suffix is specially productive in Brazilian Portuguese, giving rise to many deverbal nouns that, in context, occur with a light verb (dar ‘to give’, fazer ‘to do’, ter ‘to have’), as in dar uma pensada ‘literally: to give a thought: to think’, dar uma processada ‘literally: to give a processing; to process’. As Portuguese data evidence, affix selection is not sensitive to the distinction between rheme path objects and undergoers. In earlier works (XXX and XXX), we have already proposed that affix selection is dependent on the semantic compatibility between affixes and bases. We propose that the point is not that the verb selects one affix if the verb has a certain feature and blocks the selection of that affix if it has another one. It is not a question of all or nothing. Data show that the same verb may select ‘rival’ affixes. We propose that the semantic features of the affix must be semantically compatible with semantic features of the event structure and of the lexical-semantic structure of the base verb. Due to a co-indexation mechanism (Lieber 2004), the semantic feature of the affix will co-index with the semantic feature of the verb that is the most compatible one with its own feature. For instance, -da has as semantic features [+sudden event; +point of arrival]. If there is a verb whose event structure has a point of arrival (e.g. tosquiar ‘to shear’), then -da may co-index with it, forming tosquiada, whose meaning will be ‘sudden event focused on the point of arrival of shearing’. At the same time, the same verb has a [course of the process] feature. The suffix -mento is compatible with that feature. Thus, there is the deverbal noun tosquiamento, meaning ‘the course of the process of shearing’. Each suffix, because of its own semantic feature(s), highlights the feature of the verb it co-indexes with. Our hypothesis permits us to explain why there are so many verbs with different deverbal nouns, with different affixes. The affixes in those situations are not acting as rivals, since each one co-indexes with the feature of the base that is the most compatible one with its own feature.